High density DNA methylation array is a reliable alternative for PCR-based analysis of the MGMT promoter methylation status in glioblastoma - Braczynski-Hoog Antink, Anne Kristin; Capper, David; Jones, David T. W.; Schittenhelm, Jens Florian; Stichel, Damian; Deimling, Andreas von; Harter, Patrick Nikolaus; Mittelbronn, Michel Guy André (Pathology, research and practice, 2020)
Aim - MGMT promoter methylation status is an important biomarker predicting survival and response to chemotherapy in patients suffering from glioblastoma. Since new diagnostic methods such as methylome-based classification of brain tumors are more and more frequently performed, we aimed at comparing the suitability of calculating the MGMT promoter methylation status in a quantitative manner from the methylome profiling as compared to the classic gold standard assessment by PCR. - Methods - Our cohort consisted of 39 cases diagnosed as “glioblastoma, IDH-wildtype” of which the MGMT promoter methylation status was analyzed with both methylation-specific PCR and high density DNA methylation array using the STP-27 algorithm. Contradictory results were validated by pyrosequencing. - Results - The inter-method reliability reached 77% (kappa-coefficient: 0.58) when also cases with an inconclusive result in one or the other method were taken into account. When only cases with conclusive results in both methods were considered, a very high inter-method reliability of 91% (kappa-coefficient: 0.86) could be achieved. For “methylated” cases, no contradictory results were obtained. For the remaining two cases with discrepant results subsequent pyrosequencing analyses spoke in favor of each previously applied method once. - Conclusion - In addition to its benefits for molecular subgrouping and copy number analysis of brain tumors, DNA-methylation based classification is a highly reliable tool for the assessment of MGMT promoter methylation status in glioblastoma patients.